Wasatiyya as a higher principle of the Shariah: a civilizational approach - Ali, Mohd Mumtaz (School of Humanities, Universiti Sains Malaysia (USM), 2017)
The concept of wasatiyya (moderation), as a principle, has been recognized as the hallmark of Muslim society. But due to various reasons it has not sufficiently been in practice among Muslims at individual and collective levels. We observe trends of reactions, extremism, fanaticism and emotionalism among Muslim societies. Hence, some concentrated efforts have been started to bring the concept back into a reality as an authentic approach for Muslims individually and collectively. As a result of these serious deliberations, the concept has been substantially explained a fresh. Various approaches on its application have been identified. Despite of all these, the theme has never been perceived through the perspective of the Shariah and its higher objectives. A deep reflection on this concept make us to realize that the subject has utmost significance in the field of the Shariah as well. The recurrent use of the theme intermittently in the normative sources and its explicit emphasis in the Shariah’s injunctions and rulings make us to accept the wasatiyya as one of the higher objectives of the Shariah. Hence, this paper attempts to examine the scope of wasatiyya as a part of maqasid of the Shariah which is to be materialized at individual and collective levels as well. Moreover, this paper presents a theoretical framework of civilizational renewal on the premises of wasaÏiyya concept. For this purpose, the primary texts dealing with the theme are examined along with the views and approaches of some contemporary scholars.